2023
DOI: 10.1186/s12890-023-02713-z
|View full text |Cite
|
Sign up to set email alerts
|

Lower socioeconomic status associated with higher tuberculosis rate in South Korea

Seong-Woo Choi,
Jeong-Ja Im,
Sang-Eun Yoon
et al.

Abstract: Background Tuberculosis is an infectious disease influenced by social factors rather than a simple infectious disease. In this study, we investigated the relationship between tuberculosis rates and socioeconomic status. Methods This study was conducted using data of the 49,483 participants of the Korean National Health and Nutrition Examination Survey (KNHANES) VI–VIII (2013–2021). The relationships between tuberculosis rates and the quartiles of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…For example, one study found that higher education was associated with lower TB incidence and mortality in low- and middle-income countries [ 38 ]. Another study found that lower education was associated with higher TB prevalence [ 39 ]. However, these associations may vary depending on other factors such as socioeconomic status, health system performance, and cultural norms.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study found that higher education was associated with lower TB incidence and mortality in low- and middle-income countries [ 38 ]. Another study found that lower education was associated with higher TB prevalence [ 39 ]. However, these associations may vary depending on other factors such as socioeconomic status, health system performance, and cultural norms.…”
Section: Discussionmentioning
confidence: 99%